Multi-criteria approach in evaluating contribution of social entrepreneurship to the employment of socially-excluded groups - Džunić, Marija; Stanković, Jelena; Janković-Milić, Vesna (Technological and Economic Development of Economy, 2018)
The paper explores the potential impact of social enterprises on social exclusion. In particular, the role of social enterprises in labour market integration of socially excluded individuals is analysed within the existing theoretical and policy discourses of exclusion. Taking into account the difficulties in measuring the social impact of social enterprises, our study contributes to the quantitative literature on the performance of social enterprises, taking the number of integrated people as a measure of the impact on social exclusion. The research is based on data on the employment of marginalized groups, derived from a unique dataset collected by a recently conducted survey of social enterprises in Serbia. The original methodological framework combines statistical methods and multi-criteria decision making model, in order to evaluate the contribution of different types of enterprises to the employment of excluded individuals. Weights determination for the MCDM model is performed using entropy while TOPSIS method is applied for the ranking of the types of social enterprises according to the employment of socially excluded categories. The results indicate that enterprises for employment of persons with disabilities, citizens’ associations and cooperatives in Serbia contribute the most in integrating the socially excluded.